A Lived Experience Well-Understood: What Montesquieu’s The Spirit of the Laws Can Tell Us about Civic Learning in Higher Education - Berebon, Charles (Universitas Negeri Makassar, 2023)
This article explores how Montesquieu’s theoretical response to the perceived dangers of modern commerce can inform contemporary approaches to teaching citizenship in higher education. I argue that a Montesquieu-inspired framework for civic learning, which emphasizes a thorough study of a nation’s constitutional and positive laws, would (1) require a foundational level of scientific and economic literacy to understand how recent innovations in commercial modernity might undermine the authority of these laws if left unregulated, and (2) foster an appreciation for the laws, customs, institutions, and practices that these same innovations threaten to erode. The article concludes with practical recommendations for cultivating resilient future stewards of our self-governing republic. I contend that universities must create learning environments that inspire students to pursue diverse forms of success and recognition, particularly by imposing significant restrictions on the use of electronic devices in classrooms.